Computer algorithms in the field of wholesale power market : opportunities and challenges - Gasilina, Elvira; Zouhar, Jan, 1982-; Pavlíček, Antonín, 1977-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
For a smooth transition from separate and independent state-managed power markets to a single interconnected decentralised Pan-European market, as an integral part of power market liberalisation process, the new power market coupling principle for electricity trading has recently become an important research topic. Due to the current decarbonisation framework, increasing the production of electricity from renewable sources leads to serious problems with network load imbalance. Unpredictable level of electricity production from renewable sources, the imbalance of both the demand and the supply of electricity, hardware constraints of generation from nuclear and conventional power plants, decentralisation of electricity flow management among the EU countries, and target of preserving system maximising social welfare creates a serious optimisation problem for efficient allocation of cross-border capacities in the transmission of electricity process and evaluation of spot prices in all market bidding zones. The efficient solution for the optimisation problem is the introduction of a single unified and more flexible system for trading of electricity between European countries. EUPHEMIA (Pan-European Hybrid Electricity Market Integration Algorithm) algorithm is a single price coupling algorithm, which allows for an automatic calculation of available cross-border capacities amongst EU regions, their efficient allocation to market participants in order to achieve maximum possible social welfare, and processing coupling of bids and asks of market participants, calculating electricity prices for coupled EU regions. This thesis attempts to assess opportunities and challenges of using EUPHEMIA computer algorithm in the field of wholesale power market by identifying and analysing impacts of an introduction of EUPHEMIA algorithm to the wholesale energy spot market.
The business process of electricity trading during an explicit and implicit auction is described in order to evaluate the changes in the power market design after the introduction of the EUPHEMIA algorithm. To reveal the opportunities and challenges with EUPHEMIA algorithm application on power market, two datasets with data on the ATC, actual flow and electricity day-ahead prices for Czech Republic and other EU countries are compiled based on data from open sources (ENTSO-E Transparency platform, OTE and EPEX Spot websites). Economical metrics developed to show the effectiveness of the algorithm by reducing the number of unprofitable electricity flows, as well as by calculating the social welfare of market participants before and after the introduction of the algorithm. The linear regression method with a breakpoint introduced at the moment of transition from an explicit to an implicit auction is used to assess the behaviour of the ATC trend over time, taking into account seasonality and autocorrelation. The number of hours during the observation period, when the electricity price spread between Czech Republic and other countries was zero, is calculated to estimate the impact of the algorithm on the wholesale power market and identify opportunities and challenges of applying the implicit auction mechanism to the electricity trading process.
Vedoucí práce: Jan Zouhar
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses